2017
DOI: 10.1186/s40795-017-0183-x
|View full text |Cite
|
Sign up to set email alerts
|

National pattern of grain products consumption among Canadians in association with body weight status

Abstract: Background: Obesity in Canadian adults is showing upward trends. Consumption of whole-grains is one recommendation for the prevention of obesity. Despite the apparent nutritional and energy content differences between whole and refined grains, knowledge relating refined grains to weight gain in Canadian adults is scarce. The aim of this study was to assess the consumption of specific grain-based foods at the regional and national levels, and to evaluate the association between grain consumption with overweight… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

4
4

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 40 publications
1
5
1
1
Order By: Relevance
“…When breakfast intakes were expressed relative to breakfast’s contribution to daily energy intake, breakfasts consumed by all age groups contributed positively to intakes of milk and alternatives and grain products (especially whole grains) but under-contributed to intakes from the vegetables and fruits and meat and alternatives food groups. Canadian diets generally provide intakes of meat and alternatives and grain products that are close to the recommendations of Canada’s Food Guide [ 43 ] (although intakes of whole grains are considerably less than the recommended 50% of grain products [ 44 ]) while intakes from the vegetables and fruit and the milk and alternatives food groups generally fall below recommendations [ 43 ]. Thus, intakes of food groups at breakfast appeared to help mitigate observed shortfalls in meeting food group recommendations, although this was not true for the total vegetables and fruit group: while breakfast contributed positively to intakes of fruit and fruit juice relative to the rest of the day for the population as a whole, intakes of vegetables at breakfast were extremely low (data not shown; mean intake at breakfast was 3% of total daily vegetable intake).…”
Section: Discussionmentioning
confidence: 99%
“…When breakfast intakes were expressed relative to breakfast’s contribution to daily energy intake, breakfasts consumed by all age groups contributed positively to intakes of milk and alternatives and grain products (especially whole grains) but under-contributed to intakes from the vegetables and fruits and meat and alternatives food groups. Canadian diets generally provide intakes of meat and alternatives and grain products that are close to the recommendations of Canada’s Food Guide [ 43 ] (although intakes of whole grains are considerably less than the recommended 50% of grain products [ 44 ]) while intakes from the vegetables and fruit and the milk and alternatives food groups generally fall below recommendations [ 43 ]. Thus, intakes of food groups at breakfast appeared to help mitigate observed shortfalls in meeting food group recommendations, although this was not true for the total vegetables and fruit group: while breakfast contributed positively to intakes of fruit and fruit juice relative to the rest of the day for the population as a whole, intakes of vegetables at breakfast were extremely low (data not shown; mean intake at breakfast was 3% of total daily vegetable intake).…”
Section: Discussionmentioning
confidence: 99%
“…However, our analysis put this figure at 25.9%, which could be related to the different data collection methods used in CCHS-2004 and CCHS-2015 [35]. Additionally, our analyses indicated that about 80% of Canadian adults do not consume the recommended number of GBFs servings recommended by the Canada’s Food Guide released in 2007 [21]. If we consider the Canadas’ new food guide suggesting most of the grain intakes should be from whole grain [36] in 2015, a considerable proportion of Canadians had consumption patterns of GBFs that were far from the recommended patterns of grain consumption by Health Canada.…”
Section: Discussionmentioning
confidence: 90%
“…The analyses of the CCHS cycle 2.2 conducted by our team indicated whole grains contribute to only one-third of Canadians GBFs diets [21]. However, there have been no studies examining the detailed consumption patterns of GBFs and the contribution of these foods to the nutrient intakes of Canadian adults (aged 19 years and older).…”
Section: Introductionmentioning
confidence: 99%
“…The intake from the grains group was much lower in CHMS (2007–11) compared to CCHS 2.2 [3]. This is probably due to not including the following grain products in the CHMS FFQ food list, which are among the commonly consumed grain products in Canada [19]: quinoa, bulgur, oatmeal, cornmeal, barley, buckwheat, rye, amaranth, millet, sorghum, triticale, couscous, pretzels, popcorn, crackers, pancakes, and waffles [19, 20]. Further, the CHMS FFQ does not cover intake from aggregated foods such as pizza, which are generally not easily captured by the FFQ method [21].…”
Section: Discussionmentioning
confidence: 99%